Amylolytic Activities Produced by the Halophilic Archaeon Haloferax mediterranei Depend on the Carbon and Nitrogen Sources: A Brief Study - Perez-Pomares, F.; Bonete, M. J. (Research Perspective on Biological Science Vol. 2, 2025)
The use of starch as well as other carbohydrates is essential for the cell in order to obtain carbon and energy, mainly when it is exposed to extreme environmental conditions. The halophilic archaeon Hfx mediterranei is a good example of optimal adaptation to these limiting media, since it has been reported to use many different carbon and nitrogen sources. The adaptation of the halophilic archaeon to these media: starch, glycerol, and yeast extract maximal medium by producing glycosidic activities that may be intra- and extracellular has been extensively studied and compared. It is interesting how the organisms are able to optimally metabolize starch as a carbon and energy source, and use different nitrogen sources as nitrate or ammonium. The purification steps to obtain the many halophilic enzymes implied are those developed for decades, including ion exchange, gel affinity gel filtration chromatographies, and elution of the sample loaded in a Sepharose 4B column, by changing hydrophobic interaction. Once isolated, their kinetics at different pHs, substrates, temperatures and regulatory metabolites were determined, confirming in nearly all the cases a typical halophilic behavior, requiring high salt concentration for optimal activity and stability in a range 1.5 to 3 M NaCl., as well as certain thermophilic character, with optimal activity at 50ºC to 60ºC. When cells were grown in ammonium acetate medium, the use of a Hydroxyapatite column enabled the isolation of an excreted \(α\)-amylase; meanwhile, using affinity chromatography, a cyclodextrin glycosyltransferase was extracted. On the other hand, in a nitrate-containing medium, and using starch column chromatography, at least six different activities, with molecular masses in a range of 15 kDa to 80 kDa, were excreted in the medium, but not all of them were found in the ammonium-containing one. These enzymes displayed a different affinity for starch as a chromatographic matrix when eluted with maltose gradient, and differed in their kinetic parameters for starch as a substrate. In addition, three different amylolytic activities were detected in the cytoplasm of the organism grown in a starch-containing medium. These findings show a complex pattern of use of different enzymes to achieve a maximal profit of the sources available, also adapted to the specific media the organism has to endure, mainly the nitrogen source present in the medium. However, the assignation of each enzyme to the possible sequences in the genome could only be achieved for the cyclodextrin glycosyltransferase. For the rest of them, it is still unsolved.